2017
DOI: 10.1016/j.neuroscience.2017.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Trigeminal brainstem modulation of persistent orbicularis oculi muscle activity in a rat model of dry eye

Abstract: Altered corneal reflex activity is a common feature of dry eye disease (DE). Trigeminal sensory nerves supply the ocular surface and terminate at the trigeminal interpolaris/caudalis (ViVc) transition and spinomedullary (VcC1) regions. Although both regions contribute to corneal reflexes, their role under dry eye conditions is not well defined. This study assessed the influence of local inhibitory and excitatory amino acid neurotransmission at the ViVc transition and VcC1 regions on hypertonic saline (HS) evok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 66 publications
1
12
0
Order By: Relevance
“…Several methods have been used to estimate chronic ocular hyperalgesia in animals: spontaneous and evoked eyeblink rates, palpebral opening and forelimb eye wiping to ocular surface stimulation ( de Castro et al, 1998 ; Bates et al, 2010 ; Yorek et al, 2016 ; Fakih et al, 2019 ; Mecum et al, 2020 ). Recently, we reported that HS-evoked OOemg activity was a reliable surrogate for ocular hyperalgesia in anesthetized male rats ( Rahman et al, 2017 ). HS-evoked long duration, squint-like OOemg activity that was enhanced in DED rats, corresponded well to cornea-evoked eye wiping behavior and involved TRPV1 activation, results that were consistent with the notion of HS-evoked OOemg as a nociceptive behavior ( Bereiter et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several methods have been used to estimate chronic ocular hyperalgesia in animals: spontaneous and evoked eyeblink rates, palpebral opening and forelimb eye wiping to ocular surface stimulation ( de Castro et al, 1998 ; Bates et al, 2010 ; Yorek et al, 2016 ; Fakih et al, 2019 ; Mecum et al, 2020 ). Recently, we reported that HS-evoked OOemg activity was a reliable surrogate for ocular hyperalgesia in anesthetized male rats ( Rahman et al, 2017 ). HS-evoked long duration, squint-like OOemg activity that was enhanced in DED rats, corresponded well to cornea-evoked eye wiping behavior and involved TRPV1 activation, results that were consistent with the notion of HS-evoked OOemg as a nociceptive behavior ( Bereiter et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Rats were allowed to breathe spontaneously. The rat was placed in a stereotaxic frame and Teflon-coated copper wires (0.12 mm diameter) were implanted by a 26-gauge needle near the center of the upper and lower OO muscles, proximal to the lid margins, and grounded by a wire inserted in the neck muscle and at least 1 h elapsed before recording began ( Rahman et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Rats were anesthetized (ketamine, 90 mg/kg and xylazine, 10 mg/kg), and the subcutaneous exorbital lacrimal gland, which is located just anterior and slightly below the ear (Lorber 1993;Walcott et al 2005) ipsilateral to the OOemg electrodes, was removed. Exorbital gland removal created an~50% reduction in tearing in the ipsilateral eye (Bereiter et al 2018;Katagiri et al 2015;Meng et al 2015;Rahman et al 2015bRahman et al , 2017. This mild dry eye did not produce corneal ulcerations because rats have two additional glands that contribute to the aqueous portion of the tear film (Williams 2002).…”
Section: Methodsmentioning
confidence: 99%